1991
DOI: 10.1002/j.2161-007x.1991.tb00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Values of Psychotherapists: How Psychologists, Psychiatrists, Psychoanalysts, and Social Workers Conceptualize Good Mental Health

Abstract: Previous research suggests that laypersons differ as a function of gender and ethnicity in their views about the meaning of “mental health.” The current study examined agreement among psychotherapists about the nature of healthy psychological functioning. National samples of psychologists, psychiatrists, social workers, and psychoanalysts completed the Mental Health Values Questionnaire, a measure of value dimensions used in appraising emotional adjustment. Results indicated a relatively high degree of consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Based on a national survey of professional counselors, E. W. Kelly (1995) summarized the typical profile of counselor values as an overall content pattern that generally reflects a strong core valuing of holistichumanistic empowerment related to personal development and interpersonal or social concern. This portrait is similar to that of other mental health professionals (Haugen, Tyler, & Clark, 1991;Jensen & Bergin, 1988).…”
Section: Values In Counselingsupporting
confidence: 80%
“…Based on a national survey of professional counselors, E. W. Kelly (1995) summarized the typical profile of counselor values as an overall content pattern that generally reflects a strong core valuing of holistichumanistic empowerment related to personal development and interpersonal or social concern. This portrait is similar to that of other mental health professionals (Haugen, Tyler, & Clark, 1991;Jensen & Bergin, 1988).…”
Section: Values In Counselingsupporting
confidence: 80%
“…Knowledge in this area intends to facilitate counselor self-awareness and sensitivity to the value systems of clients (Corey & Corey, 2003). Counselor value orientations and worldviews have become prominent topics in multicultural counseling and pedagogy (e.g., Henriksen & Trusty, 2005), the therapeutic relationship (e.g., Mitchell, 1993), the mental health values of therapists (e.g., Haugen, Tyler, & Clark, 1991), and religious and spiritual counseling (e.g., Hinterkopf, 1994). Nevertheless, we were unable to find empirical studies that enriched the dialogue on the value orientations of entry-level counselor trainees in the journals of the American Counseling Association (ACA).…”
Section: Value Orientations Of Counselors and Traineesmentioning
confidence: 99%
“…2. Mental health values: Studies of mental health values of various mental health professionals have shown a generally strong consensus across a broad range of values (Jensen & Bergin, 1988;Haughen, Tyler, & Clark, 1991). It is noteworthy that neither Jensen and Bergin (1988) nor Haughen et al (1991) included professional counselors among the mental health professionals they surveyed resulting in a serious information gap about a major mental health professional group.…”
mentioning
confidence: 99%
“…Religious-spiritual values: Religion and spirituality are receiving renewed attention in counseling (Bergin, 1991;Bergin & Jensen, 1990;Ellis, 1989;Gibson & Herron, 1990;Gormally, 1990; E. W. Kelly, 1995;Shafranske & Malony, 1990;Worthington, 1989). Although research presents a mixed picture of the religious and spiritual values of mental health professionals (Haughen et al, 1991;Jensen & Bergin, 1988), a consensus emerges when these values are construed more broadly as spiritual or existential than as specifically religious (Bergin & Jensen, 1990;Shafranske & Malony, 1990). Evidence is also mixed about process and outcome effects of counselor-client similarity in this values area (Beutler & Bergan, 1990;T.…”
mentioning
confidence: 99%